The medieval towers in the landscape of Euboea: landmarks of feudalism - Loizou, Chrystalla (Journal of Greek Archaeology, 2016)
The long and narrow island of Euboea lies along the east coast of Central Greece, from the Pagasetic Gulf up to the coasts of Attica. In the hinterland of Euboea occurs an astonishing alternation of landscapes, combining extremely high mountains, low hills with a wide range of geological formations and flat fertile plains, creating scenery suitable for interaction between humans and the natural environment. The central part of the island is dominated by a mountain range with the highest peaks being Mount Dirfi and Olympus. The northern part of Euboea is largely isolated from the rest of the island and encompasses a hilly landscape dominated by the lush mountain of Kantili and the coastal plain of Histiaia. The southern part of the island is characterized by a hilly and rocky landscape with the highest peak being Mount Ochi, in the region of Karystos.